Efficient Model for Privacy Preserving Classification Of Data Streams - et. al., P Rajendra Prasad, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Privacy preserving data mining has become progressively mainstream since it permits sharing of privacy delicate data for examination purposes .So individuals have gotten progressively reluctant to share their data, regularly bringing about people either declining to share their data or giving inaccurate data. As of late, privacy preserving data mining has been concentrated broadly, on account of the wide multiplication of delicate data on the web. Data Mining manages programmed extraction of already obscure examples from a lot of data sets. These data sets ordinarily contain touchy individual data or basic business data, which thusly get presented to different gatherings during Data Mining exercises. This makes hindrance in Data Mining measure. Answer for this issue is given by Privacy preserving in data mining (PPDM). PPDM is a specific arrangement of Data Mining exercises where procedures are developed to secure privacy of the data, so the information revelation cycle can be completed without obstruction. The target of PPDM is to shield delicate data from spilling in the mining cycle alongside exact Data Mining results. The objective of this paper is to introduce the survey on different privacy preserving strategies which are useful in mining huge measure of data with sensible productivity and security.